Evaluation of time, temperature and concentration of solvent, in the extraction of bioactive compounds from carrot (daucus carota) (Research, Society and Development, 2020)
The objective of this work was to analyze the content of bioactive compounds extracted from the carrot, through an experimental design of 3 factors, 3 levels and two axial points, including extraction time (17-37-57min), temperature (30-50-70ºC) and ethanol concentration (50-65-80%). The result was expressed as a percentage. Based on the results, it can be said that time did not significantly influence the extraction of antioxidant compounds (p> 0.001), and that the temperature is directly proportional to the yield. Regarding phenolic compounds, only temperature was significant, and for flavonols, only time and proportion. The use of ethanol as a solvent showed good results when compared to the commonly used solvents, in addition to having the quality of being economically viable and food grade. Another important factor was the pre-treatment of the sample, which allowed good yield values ​​when compared to the literature.